Prototype SMS and GPS based Otoped Rental Tracking System for Car Free Day Darmo Surabaya - kridoyono, agung; Yunanda, Anton Breva; Sidqon, Mochamad; Hartono, Elvianto Dwi; Sudaryanto, Aris; Yuwono, Istantyo (Universitas Nahdlatul Ulama Surabaya, 2024)
The main problems in otoped rentals are congestion, road branches, and internet connectivity. This research aims to design and implement a simple rental tracking system for otoped at Darmo Surabaya Car Free Day, utilizing Arduino technology integrated with SMS, maps, GPS, and the SIM800L module. The system is developed to enhance the efficiency and security of otoped rentals by providing real-time tracking and location updates. The main components include an Arduino microcontroller, GPS module for location tracking, SIM800L module for SMS communication, and a map interface for visualization. The system sends location data via SMS, which can be accessed by users and administrators to monitor otoped positions and usage. The effectiveness of the system is evaluated based on its accuracy, reliability, and user satisfaction. The results indicate that the Arduino-based tracking system performs well in providing real-time updates and accurate location data, significantly improving the management of scooter rentals. This study concludes that the integration of Arduino, SMS, maps, GPS, and SIM800L is a viable solution for a simple and effective rental tracking system for electric scooters.